Reaching the peak performance zone : how to motivate yourself and others to excel - Kushel, Gerald (New York : AMACOM, 1994)
In Reaching the Peak Performance Zone, Dr. Kushel outlines a three-part process for achieving outstanding performance in yourself and others. Step by step he shows how to build that sense of self-responsibility, how to find out what motivates each member of the work group, and how to nurture potential peak performers. "Performing consistently at a high level is, in and of itself, a great pleasure," comments Dr. Kushel. "Being able to see similar performances by those who work with and for you can be even more enjoyable." Reaching the Peak Performance Zone shows you how to experience both of these pleasures by putting yourself, your team, maybe even your whole organization, in the "peak performance zone" - where excellence is not just an occasional occurrence but the status quo!
Pt. I. Becoming a Peak Performance Manager. 1. Understanding Peak Performance. 2. The Self-Responsibility Imperative. 3. The A-B-C Method of Thought Choice. 4. Profile of Peak Performing Managers -- Pt. II. Building a Self-Responsible Staff. 5. Teaching Self-Responsibility Starts with Yourself. 6. Hiring Self-Responsible People. 7. Self-Responsibility Seminars. 8. Other Teaching Methods -- Pt. III. Motivating Peak Performance. 9. The Fundamentals of Motivation. 10. Using the WIIFM Principle. 11. Motivating Good Performers to Be Even Better -- Pt. IV. Nurturing Peak Performance. 12. Mentoring. 13. Counseling. 14. Coaching. 15. Self-Coaching. 16. Starter File of Effective Thoughts -- Pt. V. Reaching the Peak Performance Zone: A Review. 17. Highlights.
Includes index.
Keywords: Employee motivation; Achievement motivation; Performance